Neuropathic pruritus: an early indicator of neuromyelitis optica spectrum disorders - Bansal, Pradeep Kumar; Nawal, C. L.; Singh, Aradhana; Chejara, Radheyshyam; Marker, Sebastian; Mangal, Pankaj (International Journal of Research in Medical Sciences, 2018)
Neuromyelitis optica is a relapsing, inflammatory astrocytopathic disorder, affecting predominantly the optic nerves and spinal cord. It is associated with antiaquaporin-4 immunoglobulin G (AQP4-IgG) in up to 70% of patients. Spinal cord involvement typically presents as a longitudinally-extensive transverse myelitis, with associated sensorimotor and sphincter dysfunction. Sensory symptoms such as numbness, dysaesthesia, pain and tonic spasms are common. Here, we present a case of a 25years old female who came to the medicine OPD, with the chief complaints of intense itching over face and forehead, which was later on progressed to quadriparesis after 3 weeks. This case highlights neuropathic pruritus as an under-recognised early feature of neuromyelitis optica.